Calculați a) (6-2/7)^2*18/8; b) (2/3)^2*[0,(3)+1/2:(-0,75)
Răspunsuri la întrebare
Răspuns de
12
a) (6-2/7)² ×18/8 =
=[(42-2)/7]² ×9/4 =
=(40/7)² ×9/4 =
=1600/49 ×9/4 =
=3600/49=(60/7)²
b) (2/3)²×[0,(3)+1/2:(-0,75)] =
=4/9×[1/3+1/2:(-3/4)] =
=4/9×[1/3+1/2×(-4/3)] =
=4/9×(1/3-2/3) =
=4/9×(-1/3) =
=-4/27
=[(42-2)/7]² ×9/4 =
=(40/7)² ×9/4 =
=1600/49 ×9/4 =
=3600/49=(60/7)²
b) (2/3)²×[0,(3)+1/2:(-0,75)] =
=4/9×[1/3+1/2:(-3/4)] =
=4/9×[1/3+1/2×(-4/3)] =
=4/9×(1/3-2/3) =
=4/9×(-1/3) =
=-4/27
Alte întrebări interesante
Limba română,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă